A2.05 Carbamylated autoantigens facilitate the break of tolerance: A novel mechanism in the pathogenesis of autoimmune arthritis. (24th February 2016) - Dekkers, JS; Verheul, MK; Stoop, JN; van Veelen, PA; Janssen, GMC; Huizinga, TW; Trouw, LA; Toes, RE
Abstract : Background and objectives: Rheumatoid arthritis is characterised by an immune response against posttranslational modified proteins, in particular citrullinated and homo-citrullinated (carbamylated) proteins. Posttranslational protein modification can result in the generation of neo-epitopes that may subsequently trigger auto-immune responses. Antibodies recognising carbamylated proteins (anti-CarP antibodies) are present in sera of RA-patients as well as in different animal models of arthritis. It is currently unknown how responding B cells interact with homo-citrullinated proteins or whether carbamylated self-proteins induce a breach of tolerance. We hypothesise that not only carbamylation of foreign, but also self-proteins can induce anti-carbamylated protein responses both at the T-cell and B-cell level, enabling T-cell dependent antibody production against carbamylated autoantigens. Materials and methods: Mice were immunised with carbamylated antigens (ovalbumin/murine albumin/murine fibrinogen) or non-modified antigens. T cell responses were studied by proliferation assays and cytokine ELISAs. Murine anti-CarP hybridomas were sequenced using single cell PCR-based antibody cloning technology. Reactivity of human anti-CarP antibodies towards CaFCS and albumin was determined for by ELISA 160 RA-patients of the Leiden Early Arthritis Cohort and controls. Results: After Ca-mAlb immunisation, mice developed high titers of anti-CarP antibodies, recognising different carbamylated foreign- and auto-antigens. In contrast, no anti-CarP antibodies were detected in mAlb immunised mice. Similar responses (i.e. anti-CarP antibody responses against carbamylated human albumin) were observed in RA-patients. Murine monoclonal anti-CarP antibodies show a similar pattern of cross-reactivity towards carbamylated antigens, together indicating that homo-citrulline is seen in a "hapten-like manner" by responding B cells. Analysis of Ig gene sequences revealed high numbers of somatic mutations, indicative of antigen-driven selection for antibody generation. T cell cultures derived from Ca-mAlb immunised mice responded to stimulation with Ca-mAlb, but not to the native protein. Conclusions: Carbamylation of both foreign as self-proteins can facilitate a breach of tolerance, resulting in formation of carbamylated protein-specific T-cell and B-cell responses in mice. In mice, homo-citrulline-residues are detected by anti-CarP-antibodies in a "hapten" like manner. Interestingly, carbamylated albumin, which is able to break tolerance in mice, is also recognised by anti-CarP antibodies in RA-patients. These data provide first evidence explaining the abundance of carbamylated self-proteins recognised by anti-CarP antibodies.